Physical Education Students' Perceptions Of The Use Of Supplements And Drugs In The World Of Sports - Olivia Dwi Cahyani; Nawafila Februyani; Ria indah Kusuma Pitaloka (International Journal of Education and Learning, 2025)
The use of supplements and medications in the world of sports has become an increasingly prominent issue, including among Physical Education students. A lack of proper understanding regarding the content, benefits, and risks of these substances can lead to dangerous misconceptions in sports practice. This study aims to examine the perceptions of Physical Education students at Nahdlatul Ulama Sunan Giri University regarding the use of supplements and medications in sports, as well as the factors that influence those perceptions. The research employs a descriptive qualitative approach with a field study method. Data were collected through in-depth interviews, observations, and documentation involving six purposively selected informants. The results show that students tend to be permissive toward the use of supplements and morally reject the use of medications; however, their understanding remains limited in terms of scientific and regulatory aspects. Factors influencing their perceptions include personal experience, peer influence, social media, and the limited coverage of the topic in academic courses. These findings highlight the need to strengthen the curriculum and health education to foster critical understanding and responsible attitudes regarding the use of performance-enhancing substances in sports.